The i-Walk Lightweight Assistive Rollator: First Evaluation Study - Moustris, George; Kardaris, Nikolaos; Tsiami, Antigoni; Chalvatzaki, Georgia; Koutras, Petros; Dometios, Athanasios; Oikonomou, Paris; Tzafestas, Costas; Maragos, Petros; Efthimiou, Eleni; Papageorgiou, Xanthi; Fotinea, Stavroula-Evita; et al. (Frontiers in Robotics and AI, 2021)
Robots can play a significant role as assistive devices for people with movement impairment and mild cognitive deficit. In this paper we present an overview of the lightweight i-Walk intelligent robotic rollator, which offers cognitive and mobility assistance to the elderly and to people with light to moderate mobility impairment. The utility, usability, safety and technical performance of the device is investigated through a clinical study, which took place at a rehabilitation center in Greece involving real patients with mild to moderate cognitive and mobility impairment. This first evaluation study comprised a set of scenarios in a number of pre-defined use cases, including physical rehabilitation exercises, as well as mobility and ambulation involved in typical daily living activities of the patients. The design and implementation of this study is discussed in detail, along with the obtained results, which include both an objective and a subjective evaluation of the system operation, based on a set of technical performance measures and a validated questionnaire for the analysis of qualitative data, respectively. The study shows that the technical modules performed satisfactory under real conditions, and that the users generally hold very positive views of the platform, considering it safe and reliable.